SISTEM INFORMASI SEKOLAH BERBASIS CLOUD PADA DINAS PENDIDIKAN KABUPATEN HUMBANG HASUNDUTAN - Jimmy F. Naibaho; Mendarissan Aritonang; Keefin Reynaldo Silaban (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The development of science and technology is currently growing so rapidly. All of it is developed with the aim of providing convenience for humans in carrying out their duties and interests. Good utilization of technology will be able to help various kinds of work activities including learning activities. In terms of data storage, currently we still use physical storage media such as hard drives and flash drives to store and share files. Because of the large amount of school data that will be managed, it is necessary to use media for data retrieval and data storage that can be used anytime and anywhere when needed and has maximum storage with the use of relatively cheaper costs. The solution to the above needs is a cloud computing-based school information system design that is used to input school data, student data, teacher data and educational activities and is able to produce the information needed by the education office. Designing a school information system using cloud computing has many benefits. The benefits that can be obtained through cloud system-based technology such as cost savings, easy access to data because all data is stored on a server centrally, and also better data security.